Changes in severity of depressive symptoms and mortality: the Italian Longitudinal Study on Aging - Scafato, E.; Galluzzo, L.; Ghirini, S.; Gandin, C.; Rossi, A.; Solfrizzi, V.; Panza, F.; Di Carlo, A.; Maggi, S.; Farchi, G. (Psychological medicine, 2012)
Depression is recognized as being associated with increased mortality. However, there has been little previous research on the impact of longitudinal changes in late-life depressive symptoms on mortality, and of their remission in particular. As part of a prospective, population-based study on a random sample of 5632 subjects aged 65-84 years, with a 10-year follow-up of vital status, depressive symptoms were assessed by the 30-item Italian version of the Geriatric Depression Scale (GDS). The number of participants in the GDS measurements was 3214 at baseline and 2070 at the second survey, 3 years later. Longitudinal changes in depressive symptoms (stable, remitted, worsened) were examined in participants in both evaluations (n=1941). Mortality hazard ratios (MHRs) according to severity of symptoms and their changes over time were obtained by means of Cox proportional hazards regression models, adjusting for age and other potentially confounding factors. Severity is significantly associated with excess mortality in both genders. Compared to the stability of depressive symptoms, a worsened condition shows a higher 7-year mortality risk [MHR 1.46, 95% confidence interval (CI) 1.15-1.84], whereas remission reduces by about 40% the risk of mortality in both genders (women MHR 0.55, 95% CI 0.32-0.95; men MHR 0.59, 95% CI 0.37-0.93). Neither sociodemographic nor medical confounders significantly modified these associations. Consistent with previous reports, the severity and persistence of depression are associated with higher mortality risks. Our findings extend the magnitude of the association demonstrating that remission of symptoms is related to a significant reduction in mortality, highlighting the need to enhance case-finding and successful treatment of late-life depression.